THE INFLUENCE OF DIGITALIZATION AND HUMAN RESOURCE MANAGEMENT ON THE COMPETITIVENESS OF MSMES IN GORONTALO - Mahadi, Nur Rizky Putri; Maintji, Mohamad Rizki; Hidayah, Magfira Nurul; Haju, Fadel (LP2M Universitas Bina Mandiri Gorontalo, 2025)
Digital transformation has become a global phenomenon that compels Micro, Small, and Medium Enterprises (MSMEs) to adapt in order to remain competitive. However, field evidence suggests that digitalization does not necessarily enhance competitiveness unless accompanied by strengthened human resource (HR) capabilities. This study aims to analyze the effects of digitalization and HR management on MSME competitiveness using a quantitative method and Structural Equation Modeling–Partial Least Square (SEM-PLS) with 59 MSME respondents. The analysis reveals that HR management has a significant effect on competitiveness, with a t-statistic of 6.985 and a p-value of 0.000. Conversely, digitalization shows no significant influence, with a t-statistic of 0.816 and a p-value of 0.415. These findings affirm that MSME competitiveness is largely driven by internal factors such as HR training, leadership, and a productive work culture. Meanwhile, digitalization will only yield optimal outcomes when supported by skilled human resources and well-directed organizational strategies. This research contributes to the strategic understanding of strengthening MSME competitiveness and serves as a reference for HR-based MSME development policies.